Alcohol‐Related Liver Disease: Areas of Consensus, Unmet Needs and Opportunities for Further Study. Issue 5 (15th January 2019) - Szabo, Gyongyi; Kamath, Patrick S.; Shah, Vijay H.; Thursz, Mark; Mathurin, Philippe
Abstract: A joint meeting of the European Association for the Study of the Liver (EASL) and the American Association for the Study of Liver Diseases (AASLD) was held in London on September 30 and October 1, 2017. The goals of the meeting were to identify areas of broad agreement and disagreement, develop consensus, and determine future directions to ultimately reduce the burden, morbidity, and mortality of alcohol‐related liver disease (previously termed alcoholic liver disease). The specific aims of the meeting were to identify unmet needs and areas for future investigation, in order to reduce alcohol consumption, develop markers for diagnosis and prognosis of disease, and create a framework to test novel pharmacological agents with pre‐specified treatment endpoints. A table summary of these goals and aims is provided in the context of epidemiology, current management strategies, next steps for future trials and translational science.